2021
DOI: 10.3389/fcvm.2021.740526
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal-Associated Protein Transmembrane 5 Functions as a Novel Negative Regulator of Pathological Cardiac Hypertrophy

Abstract: Lysosomal-associated protein transmembrane 5 (LAPTM5) is mainly expressed in immune cells and has been reported to regulate inflammation, apoptosis and autophagy. Although LAPTM5 is expressed in the heart, whether LAPTM5 plays a role in regulating cardiac function remains unknown. Here, we show that the expression of LAPTM5 is dramatically decreased in murine hypertrophic hearts and isolated hypertrophic cardiomyocytes. In this study, we investigated the role of LAPTM5 in pathological cardiac hypertrophy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…concluded that LAPTM5 was involved in pathological cardiac hypertrophy and LAPTM5 deletion aggravated pressure load-induced myocardial hypertrophy and heart failure through MEK-ERK1/2 pathway in mice, as evidenced by changed echocardiographic parameters [14]. We analyze that different animal models, disease duration, and signaling pathways involved are the reasons for the differential role of LAPTM5 in the heart diseases.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…concluded that LAPTM5 was involved in pathological cardiac hypertrophy and LAPTM5 deletion aggravated pressure load-induced myocardial hypertrophy and heart failure through MEK-ERK1/2 pathway in mice, as evidenced by changed echocardiographic parameters [14]. We analyze that different animal models, disease duration, and signaling pathways involved are the reasons for the differential role of LAPTM5 in the heart diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Our result showed that the inhibition of LAPTM5 could suppress the enhancement of MCP-1 and CD86 caused by MI. However, except for macrophages, LAPTM5 was also shown to be present in cardiomyocytes, indicating its widespread expression [14]. We speculated that the mechanism of LAPTM5 knockdown alleviating MI might be associated with a variety of cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In CD40 positive glioblastoma, LAPTM5 expression could suppress tumor growth by inhibiting CD40-mediated activation of NF-κB ( Berberich et al, 2020 ). Furthermore, LAPTM5 could play an important protective role in pathological myocardial hypertrophy through the Rac1-MEK-ERK1/2 pathway ( Gao et al, 2021 ). On the other hand, in some previous studies, LAPTM5 has been shown to negatively regulate cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…As a lysosomal transmembrane protein, LAPTM5 is widely involved in various cell functions, including protein transport, immune cell activation, signal pathway activation, autophagy, and oxidative stress [9,[15][16][17][18][19][20]. LAPTM5 is also widely involved in the progression of various cellular activities and signaling pathways.…”
Section: Discussionmentioning
confidence: 99%